Efficacy and safety of canagliflozin in patients with type 2 diabetes mellitus living in hot climates. Issue 9 (September 2016) - John, Mathew; Cerdas, Sonia; Violante, Rafael; Deerochanawong, Chaicharn; Hassanein, Mohamed; Slee, April; Canovatchel, William; Hamilton, Gill
Summary: Aims: Patients with type 2 diabetes mellitus (T2DM) have increased risk of adverse events (AEs; e.g. dehydration, hypoglycaemia) in hot weather. This analysis assessed the efficacy and safety of canagliflozin, a sodium glucose co‐transporter 2 (SGLT2) inhibitor, in patients with T2DM who live in hot climates. Methods: This post hoc analysis evaluated patients with T2DM using pooled data from four 26‐week, placebo‐controlled studies (N=2, 313) and data from a 104‐week, active‐controlled study (add‐on to metformin vs glimepiride; N=1, 450). Changes in HbA1c, fasting plasma glucose (FPG), body weight and blood pressure (BP) were assessed in subsets of patients living in hot climates (pooled, placebo‐controlled studies, n=611; active‐controlled study, n=307) and those living in other climates (i.e. other climate subset; pooled, placebo‐controlled studies, n=1, 702; active‐controlled study, n=1, 143). Safety was assessed based on AE reports. Results: Canagliflozin 100 and 300 mg lowered HbA1c, FPG, body weight and BP vs placebo over 26 weeks and glimepiride over 104 weeks in the hot climate subsets. Canagliflozin was generally well tolerated in the hot climate subsets, with a higher incidence of AEs related to the mechanism of SGLT2 inhibition (i.e. genital mycotic infections). Volume depletion–related AEs were low across groups. Conclusion: Canagliflozin improved glycaemic control, lowered body weight and BP, and was generally well tolerated in patients with T2DM living in hot climates compared with placebo over 26 weeks or glimepiride over 104 weeks. Clinical Trials registration:ClinicalTrials.gov NCT01081834, NCT01106677, NCT01106625, NCT01106690, NCT00968812.